(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This study explores the manifestation and functions of gendered language in English fashion magazines from a linguistic perspective. It examines how lexical choices, stylistic devices, and discursive strategies contribute to the construction and reinforcement of gender identities within fashion discourse. The research is based on a qualitative analysis of selected fashion magazine articles, focusing on gender-specific vocabulary, evaluative adjectives, and metaphorical expressions. Particular attention is paid to how femininity and masculinity are linguistically framed, as well as how language reflects broader socio-cultural norms and expectations. The findings demonstrate that gendered language in fashion media not only mirrors societal ideologies but also actively shapes readers’ perceptions of identity, beauty, and style.